EFEKTIVITAS PENGELOLAAN MASJID SEBAGAI SARANA PENDIDIKAN DI MASJID AL-MUSANNIF DELI SERDANG - M. Yasin (Hijri, 2019)
Whereas inguaranteeing the validity of the data the authors use credibility, transferability,dependability, and confirmability. The results of the study: 1. The function of theAl-Musannif Mosque as a Da'wah practice, namely Da'wah activities such asroutine recitation and sermons, as the practice of taklim wa taklum namely as aplace of learning and teaching such as reciting Maghrib, as a practice of dhikr andworship which is a center of practice of dhikr and worship like pray five times aday one night, and as a Wisdom Practice that is serving the community. 2 Thereligious education program is a routine recitation for fathers and mothers, themidday prayer and recitation, the recitation maghrib program for teenagers andchildren. 3. Those involved in religious education at the Al-Musannif Mosque areall elements of management, both the Foundation and the Congregation of the AlMusannifMosque. 4. Factors that support the Al-Musannif mosque program arethe Chairperson of the Foundation, the Community, Management elements andcleaning of the Al-Musannif Mosque. 5. There are no inhibiting factors.